Subcellular distribution of thyroid hormone receptor beta in ovarian cancer - Heublein, Sabine; Jeschke, Udo; Sattler, Cornelia; Kuhn, Christina; Hester, Anna; Czogalla, Bastian; Trillsch, Fabian; Mahner, Sven; Mayr, Doris; Schmoeckel, Elisa; Ditsch, Nina (International journal of molecular sciences, 2022)
Background: Since the most well-known function of thyroid hormone receptors (TRs) relies on their ability to act as ligand-activated transcription factors, their subcellular localization has been recognized to be relevant for their biological meaning. The current study aimed to determine the prevalence and subcellular distribution of TR beta and TR beta-1 in ovarian cancer (OC). Methods: Tissue was collected from 153 patients that had undergone surgery due to OC at the Department of Obstetrics and Gynaecology of the Ludwig-Maximilians-University Munich. Immunohistochemistry detecting TR beta and TR beta-1 was performed. Staining signals were quantified and tested for association with clinico-pathological parameters including overall survival (OS). Results: The subcellular distribution of TR beta and TR beta-1 differed among histologic subtypes, grade and FIGO stage. TR beta positivity was strongly linked to shortened overall survival (p < 0.001). Strikingly, this shortened OS was mainly attributed to those cases showing complete (p = 0.005) or incomplete shift of TR beta to the cytoplasm (p < 0.001). Significance was lost in multivariate testing. Conclusions: Cytoplasmatic localization of TR beta was associated with reduced OS, at least in univariate analysis. Since TRs have long been supposed to mainly function via the regulation of gene transcription in the nucleus, cytoplasmatic shifting might be interpreted as a regulator of their activity.
Gesehen am 05.04.2022